Conor Newman - Newman, Conor (Irish Journal of Arts Management and Cultural Policy, 2015)
Conor Newman, archaeologist, academic, and then chairman of the Heritage Council, wanted to drive home the message that investment in culture is investment in society and that cultural education should lie at the heart of cultural policy Thank you very much to the organisers for inviting me to be here. I’m not going to speak from the perspective of the Heritage Council, per se, because this is about cultural policy; it is not about any one particular group of people.